If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -7x = 1 + -6x Solving -4 + -7x = 1 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -4 + -7x + 6x = 1 + -6x + 6x Combine like terms: -7x + 6x = -1x -4 + -1x = 1 + -6x + 6x Combine like terms: -6x + 6x = 0 -4 + -1x = 1 + 0 -4 + -1x = 1 Add '4' to each side of the equation. -4 + 4 + -1x = 1 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 1 + 4 -1x = 1 + 4 Combine like terms: 1 + 4 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| (5n-1)(n+7)=0 | | 8-2(4x+9)=6x-4(m-5) | | 15-z=45 | | 9x+17=8x-41 | | -4y+8=-8y-12 | | 6x-6=14x-14 | | -14-r-6r=r+8 | | 2210=r(34) | | 42=2+6 | | 9-4b=6-5b | | 6-4(5+3y)=0 | | 8-1/2(-m-1) | | M+6=2m+11 | | 7v-15+7v=7v+48 | | 23=32x-425 | | 1680=336t | | 5(9x+6)=45x-4 | | 0.5x=-70 | | 3lx-1l=15 | | (3x+25)+(x-5)+x=180 | | -5-8=-13x-4 | | 2x+105=-3x+130 | | 7n+3=8+8n | | f(a+1)=(a+1)+8 | | a-43+a-43+w+43=a | | 9x+8=9x-2 | | 15*3-25+10= | | u+u+3=u+46 | | 3x-5(x-4)=-5+4x+13 | | 3x+9x-7=3(4x+4) | | 8t+40+16t-49=18t+23 | | 18x-12=3x^2 |